"Sofa and Facebook or tent and Syntagma": understanding global resistance movements from Syntagma to Tahrir. Issue 1 (1st January 2016) - Bilgiç, Ali
Abstract : This article proposes a conceptual guideline with the objective of understanding the political, economic and social complexities of contemporary street/square protests. It will be argued that contemporary protest movements can be understood from a conceptual perspective that effectively integrates individuals (their minds and bodies) and spaces to the approach of "multitude". This guideline consists of three moves: conceptualizing individualistic dimension; space dimension; and collective dimension. In the first section, resisting individuals as cognitive and material beings with the acknowledgement of their multiple subjectivities will be discussed. As the second pillar of the movements, the relationship between resisting individuals and space of resistance will be unpacked. It will be highlighted that the contemporary resistance movements develop a novel relationship with the space they occupy by respatializing it as "home of resistance". Finally, the multitude approach will be discussed in relation to the radical democratic approach in order to conceptualize the collective dimension of the movements.